2014
DOI: 10.5815/ijmecs.2014.08.02
|View full text |Cite
|
Sign up to set email alerts
|

Specialization Impact on Internet Resource Usage: Omani Undergraduate Learner’s Perspectives

Abstract: The current educational processes need various tools and technological supports in order to attain the required level of knowledge. The learning processes have been simplified with the help of different resources including internet resources. The usage of internet resources usage depends on the learner's requirements in the field of study. This research had identified the significant impacts of the specialization of the learners on the internet resource usage. Also, the paper identified some specializations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…The findings of this study is inconsistent with the previous study of Tayo (2015) whose study posited that pre-service teachers in Chemistry department have a very good perception of the use of LMS while, History department have a relatively little/skimpy insight on the use of LMS. The present study also contradicts the previous study of Sriram (2014) whose study showed that students of Information Technology specialization had greater impact in using internet resources for learning when equated to others at undergraduate levels.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
“…The findings of this study is inconsistent with the previous study of Tayo (2015) whose study posited that pre-service teachers in Chemistry department have a very good perception of the use of LMS while, History department have a relatively little/skimpy insight on the use of LMS. The present study also contradicts the previous study of Sriram (2014) whose study showed that students of Information Technology specialization had greater impact in using internet resources for learning when equated to others at undergraduate levels.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
“…Exhibition agglomeration generally includes exhibition venues, exhibition service enterprises, exhibition projects and related service formats derived from the exhibition industry. The high concentration of enterprises in different links of the industrial chain brings high efficiency, convenience and intensification to the exhibition industry, which also means specialization, branding and democratization [9]. Exhibition agglomeration zones within cities are generally formed with exhibition halls as the core.…”
Section: A Industry Supportmentioning
confidence: 99%
“…Sriram (2014) conducted a study on impact of internet resources, one of the major information technology development, and identified that in Omani higher education specializations of the learners have significant impact on the usage of technology in learning processes [15]. Robles (2013) identified that the instructors need to identify the various opportunities to integrate appropriate educational tools to suits to their learning preferences, as the internet dependencies are increasing in this modern world [16].…”
Section: Literature Reviewmentioning
confidence: 99%